THE ROLE OF DIGITAL STORYTELLING IN IMPROVING WRITING SKILLS - Qayumova Gulsanam Sadriddin qizi (Journal of new century innovations, 2024)
Abstract: This study explores the role of digital storytelling in enhancing writing skills among students. By integrating multimedia elements, digital storytelling fosters engagement, creativity, and critical thinking. This research investigates the impact of digital storytelling on students' writing abilities through a mixed-methods approach, analyzing quantitative improvements in writing scores and qualitative feedback from participants. The findings indicate significant improvements in writing proficiency and increased motivation among students, highlighting the potential of digital storytelling as an effective pedagogical tool.